Sistema de tesorería y procesos de gestión en el Hospital Regional de Loreto Felipe Arriola Iglesias; Iquitos, 2024 - Aguilar Marquez, Juan Carlos (2024)
The objective of this research was to determine the relationship that exists in the Treasury System and the management processes of the Regional Hospital of Loreto, Period 2024, used as a type of quantitative research, non-experimental design and type of transactional design of correlational scope; with a study population of 49 working officials from the different administrative areas of the Loreto Regional Hospital, concluding that the correlation coefficient of 0.534 suggests a medium positive correlation between the variable Treasury System and Management Process, this means that, In general, when one variable increases, the other tends to increase as well, but not in a perfectly proportional way. The closer the value is to 1, the stronger the positive correlation, the bilateral significance value is 0.000 indicates that the correlation is statistically significant at a very low significance level (less than 0.001), in simple terms this means that It is highly unlikely that the observed correlation is the result of chance. The probability that this correlation is a coincidence is extremely low; Therefore, the data suggest that there is a significant positive correlation between the variables analyzed, and this correlation is not due to chance; There is a statistically significant relationship between the variables.